Reliability and Sensitivity of Performance Tests in Adult Female Football Players - Mainer-Pardos, Elena; Gonzalo-Skok, Oliver (International Journal of Sports Medicine, 2025)
This study evaluated the reliability, sensitivity, and performance changes in physical tests in highly trained adult female football players over the course of a competitive season. Twenty players (21.1±2.72 years) participated in this study. Tests included bilateral and unilateral countermovement jumps, unilateral horizontal jumps, 40-m linear sprints, and change-of-direction (COD) tests (COD180° and V-cut). Relative and absolute reliabilities were analyzed. Sensitivity was determined by comparing the smallest worthwhile change to the typical error of measurement and, in addition, changes in performance over the season were assessed in short-, medium-, and long-term periods. Results demonstrated high reliability across all tests, with intraclass correlation coefficient values ranging from 0.70 to 0.94 and coefficient of variation (CV) below 5%, meeting a priori reliability criteria. Vertical jumping exhibited the highest reliability (0.89–0.92) and was sensitive in detecting moderate-to-large changes. COD tests showed moderate-to-high reliability (0.70–0.89), with CODR180° sensitive to seasonal adaptations. Sprint tests also displayed good reliability (0.80–0.94); however, their sensitivity was limited. Notably, the unilateral jump tests and CODR180° exceeded CV thresholds, highlighting their potential to monitor significant improvements over time. Unilateral and COD-specific assessments emerged as particularly valuable for detecting performance changes, underscoring the need for sport-specific testing protocols in women's football.
Keywords: soccer; power; linear speed; change of direction; women